ENJOYABLE LEARNING USING SONG MEDIA WITH APIK TECHNIQUES - Angga Fitriyono (Literasi Nusantara, 2021)
Learning arts and culture, especially music, is a learning that requires practice. But before doing practice, of course, there must be a theory that underlies it first, or it can be simultaneously when learning theory includes elements of practice too. The role of the teacher as a facilitator is very important, because it is from the teacher that knowledge that was initially only imagined by students, becomes a real reality. This is what underlies the researchers to develop a learning method that can stimulate student activity and make the classroom atmosphere come alive. This method is called Enjoyable Learning, which is a method that develops songs from basic musical knowledge and then teaches them through singing. The development method in this study uses the 4-D development method. This method consists of 4 stages of development, namely Define, Design, Develop, and Disseminate, namely defining, designing, developing, and distributing. However, due to the limited time of the study, the researcher only carried out research until the Develop stage, so that the development method in this study was modified by the researcher to be 3-D. Small-scale trials were conducted on two X graders at SMAN 1 Baureno. A large-scale trial was conducted on all X graders at SMAN 1 Baureno. Based on the results of data analysis, it can be concluded that the development of the Enjoyable Learning learning method using song media on basic music knowledge material uses the APIK technique to package material using interesting, easy to teach and make the class more lively. Suggestions for teachers, to make music learning easier in schools, teachers can use appropriate learning methods, one of which is the Enjoyable Learning method.